Commemoration for Jack Dunitz’s 100th Birthday on 29 March 2023 — Famous Friends - Jack David Dunitz (Molecular Frontiers Journal, 2023)
I intend to set down here some details of my interaction with these remarkable men and women. Since their scientific merits are well known, I need not discuss them here but shall restrict myself as far as possible to my own personal interaction with them. In the first place, I wish to stress that I have never “collected” Nobel Prize winners, never tried to contact scientists simply because they were already in this elevated category. With one or two exceptions, the scientists I mention in these pages had not yet made the journey to Stockholm at the time I became acquainted with them. Rather, it seems that throughout my career I have had the good fortune to have had contact with people who were destined to make important contributions to the progress of science. Lucky Jack!